Aesthetic theory : a philosophy of beauty and art - Lorand, Ruth (Routledge studies in twentieth century philosophy., 2000)
Aesthetic Order challenges contemporary theories of aesthetics, offering the idea of beauty as quantitative yet different from the traditional discursive order. It will be of importance to all interested in aesthetic theory.